2012
DOI: 10.1111/j.1365-2133.2012.10906.x
|View full text |Cite
|
Sign up to set email alerts
|

The south-east Scotland dermatology workload study: 30 years’ analysis

Abstract: Demand for dermatology continues to increase: new referrals have risen by 134% in 30 years, with a 36% increase in the last 5 years, despite corresponding population increases of 5·3% and 3%, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 20 publications
(30 reference statements)
1
21
1
Order By: Relevance
“…It has been shown previously that GPs' clinical diagnostic concordance with dermatologists for common inflammatory dermatoses is good (acne 94%; psoriasis 89%; and atopic dermatitis 77%), but their diagnostic concordance for the common skin malignancies is poorer (BCC 43%; SCC e467 British Journal of General Practice, August 2014 30%; and MM 14%). 12 The key findings from this study are, in the treatment of common skin cancers in primary care in east and south-east Scotland, that smaller lesions are excised in primary care, that these are less commonly in the head and neck regions, and that excision rates are inferior in terms of complete excision and adequate excision margins compared with secondary care dermatologists and plastic surgeons. The findings of poorer recognition of skin malignancy by GPs and poorer quality of skin cancer surgery in primary care compared with secondary care have been reported in other UK studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown previously that GPs' clinical diagnostic concordance with dermatologists for common inflammatory dermatoses is good (acne 94%; psoriasis 89%; and atopic dermatitis 77%), but their diagnostic concordance for the common skin malignancies is poorer (BCC 43%; SCC e467 British Journal of General Practice, August 2014 30%; and MM 14%). 12 The key findings from this study are, in the treatment of common skin cancers in primary care in east and south-east Scotland, that smaller lesions are excised in primary care, that these are less commonly in the head and neck regions, and that excision rates are inferior in terms of complete excision and adequate excision margins compared with secondary care dermatologists and plastic surgeons. The findings of poorer recognition of skin malignancy by GPs and poorer quality of skin cancer surgery in primary care compared with secondary care have been reported in other UK studies.…”
Section: Discussionmentioning
confidence: 99%
“…These two time periods were used to provide comparable numbers of primary care and secondary care cases, and the month of November for skin specialists was chosen to correspond with the most recent 5-yearly detailed assessments of south-east Scotland dermatology outpatient activity. 12 Data obtained included age, sex, diagnosis, maximum diameter of lesion, site of specimen, histological clearance, excision margin, and the specialty of the medical practitioner performing the surgery. Non-invasive premalignant lesions were excluded (for example melanoma-in-situ, SCC-in-situ).…”
Section: Methodsmentioning
confidence: 99%
“…18 Coding in the GPRD does not differentiate between erythematotelangiectatic and papulopustular rosacea, and our study population is likely to comprise an over-representation of more severe papulopustular rosacea patients. 18 Despite this potential for under diagnosis and some degree of potential disease misclassification, a 74% concordance of rosacea diagnoses between dermatologists and the referring GPs has been shown in a cross-sectional study from South East Scotland, 29 providing reassurance that the validity of rosacea diagnoses in the GPRD is sufficiently good. Secondly, the likelihood of being diagnosed with rosacea may increase with increasing medical attention, which is the case for patients with diagnosed psychiatric illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…Dermatitis makes up to 23% of diagnoses made in patients presenting with skin complaints 6. One study looking at referrals to secondary-care dermatology services in Scotland demonstrated a 134% increase in new referrals in the past 30 years, with a referral rate now of 23.2/1000 population per annum 7. Fifty-eight per cent of referrals were for diagnosis,7 and hence some of this increase in the number of patients seen could be attributed to a lack of dermatology training in undergraduate medical curricula and in postgraduate training programmes with a consequent lack of knowledge in primary and secondary care 7 8…”
Section: Introductionmentioning
confidence: 99%